2017
DOI: 10.1007/s10498-017-9310-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Assessment of CO2–Carbonic Acid System Dynamics in a Pristine Coral Reef Ecosystem, French Frigate Shoals, Northwestern Hawaiian Islands

Abstract: Observations of surface seawater fugacity of carbon dioxide (fCO 2 ) and pH were collected over a period of several days at French Frigate Shoals (FFS) in the Northwestern Hawaiian Islands (NWHI) in order to gain an understanding of the natural spatiotemporal variability of the marine inorganic carbon system in a pristine coral reef ecosystem. These data show clear island-to-open ocean gradients in fCO 2 and total alkalinity that can be measured 10-20 km offshore, indicating that metabolic processes influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Changes to DIC and δ 13 C at the surface agree closely with prior reports in which components of the inorganic carbon system exhibit strong diel dynamics at our site (Wootton et al ) and at other coastal sites in the California Current (Frieder et al ; Kapsenberg and Hofmann ). This study joins other, recent studies of the carbon cycle in coastal ecosystems that have demonstrated relatively dynamic patterns (Feely et al ; Hofmann et al ; Wootton and Pfister ; Andersson et al 2014; Kealoha et al ) and the potential for increasing variability (Schulz and Riebesell ), indicating that increased analyses of carbon system parameters are needed.…”
Section: Discussionsupporting
confidence: 82%
“…Changes to DIC and δ 13 C at the surface agree closely with prior reports in which components of the inorganic carbon system exhibit strong diel dynamics at our site (Wootton et al ) and at other coastal sites in the California Current (Frieder et al ; Kapsenberg and Hofmann ). This study joins other, recent studies of the carbon cycle in coastal ecosystems that have demonstrated relatively dynamic patterns (Feely et al ; Hofmann et al ; Wootton and Pfister ; Andersson et al 2014; Kealoha et al ) and the potential for increasing variability (Schulz and Riebesell ), indicating that increased analyses of carbon system parameters are needed.…”
Section: Discussionsupporting
confidence: 82%
“…It is well understood by earlier studies that the interaction of reef metabolism and the circulation over the reefs leads to large biogeochemical variations, especially on diel scales (Suzuki and Kawahata, 1999;Bates, 2002;Suzuki and Kawahata, 2003;Manzello, 2010;Anthony et al, 2011;Kleypas et al, 2011;Gray et al, 2012;Falter et al, 2013;Teneva et al, 2013;Andersson et al, 2014;Albright et al, 2015;Kealoha et al, 2017;Takeshita et al, 2018;Yan et al, 2018). But our work provides new insights about the nature of this variability.…”
Section: Spatio-temporal Variability and The Emergence Of A Mosaicmentioning
confidence: 54%
“…The local environmental conditions coral reefs experience can deviate substantially from those of the open ocean, especially for the seawater's carbonate system parameters, such as dissolved inorganic carbon (DIC), total alkalinity (TA), pH (-log([H + ])), the partial pressure of CO 2 (pCO 2 ), or the saturation state with respect to the mineral CaCO 3 aragonite, W a (Manzello, 2010;Gray et al, 2012;Kealoha et al, 2017;Takeshita et al, 2018;Yan et al, 2018). This is a consequence of the interplay between coral metabolism altering the seawater chemistry in the overlying waters and the transport and mixing of the water across the reef (Anthony et al, 2011;Kleypas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%